High-resolution live imaging of tardigrade response to anoxia - Haapanen-Saaristo, Anna-Mari; Calhim, Sara; Paatero, Ilkka (Elsevier BV, 2025)
Tardigrades are well-known for their ability to tolerate extreme environmental conditions such as heat, drought and lack of oxygen by undergoing cryptobiosis. The molecular responses to stress have been studied in detail, but the physiological and morphogenetic changes during cryptobiosis are less understood. We developed new live high-resolution fluorescence microscopy protocols to visualize the tardigrade response to lack of oxygen-anoxybiosis. High-resolution time-lapse imaging enabled analysis of cellular morphology and tracking of cell movements during anoxybiosis. These analyses revealed considerable changes in morphology, composition and movement of storage cells. Our observations and new imaging protocols can be used to study morphological and cellular response to stress in tardigrades.